Desenvolvimento sustentável e as políticas públicas ambientais no Brasil: um mapeamento de influências conceituais - Marques, Ademar de Oliveira (2018)
The sixties’were and will be remembered, for several generations, as the world’s awaking and facing the obvious and extremely grave environmental crisis, which was originated in the decades before, by which the man kind was passing and that, in the following decades, due to a series of disasters and environmental unbalances, only got worse, as a result of the western world developing model, becoming a factor of major concern in the “developed” and “in developing” countries, as well as in the scientific community, taking them to rethink new strategies to face this problem worldwide. This study purpose is to catalogue the main international events that contributed for the environmental problem debate and for the environment concept construction, able to conciliate: economic development, natural resources efficient use, and social equality. Those facts, the global events and the environmental development definition influenced, as a new world order, the countries environm ental legal framework and the environmental policies built at a global scale, especially in Brazil. Therefore, the aim of this study, through the analysis of three major Brazilian laws, is that those events and the sustainable development concept are present.